Risk In Islamic Banking and Islamicity Performance Index - Kartiningsih Susilowati; Falikhatun Falikhatun (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to examine the impact of financing risk, liquidity risk, and operational risk on the Islamicity performance index. We also set bank size as a control variable. The dummy variable is used as an influence on financing risk before and during the Covid-19 pandemic. Our data were analyzed using panel data regression analysis. Quantitative research in the form of financial statements of Islamic commercial banks in Indonesia for 2014-2021 was selected as our sample with a total of 69 observations. We found that, one of the three variables is significant. Financing risk has no effect on the profit sharing ratio, liquidity risk has an insignificant positive effect on the profit sharing ratio, and operational risk has a significant positive effect on the profit sharing ratio. This study can be used as a reference, evaluation, and source of improvement for Islamic banking in making the right decision to set loan prices, as well as applying good risk management methods.